Edukasi Interaktif untuk Meningkatkan Pengetahuan Ibu Hamil tentang Komplikasi Kehamilan dan Pencegahan Stunting di Puskesmas Pauh Padang: Improving Pregnant Women’s Knowledge of Pregnancy Complications and Stunting Prevention through Interactive Education at Pauh Primary Health Center, Padang - Dovy Djanas; Defrin; Nelvianti Nelson; Syamel Muhammad; Puja Agung Antonius; Ardiles; Danil Armand; Zeino Fridsto; Subhan Arif Rahman; Aswin Boy Pratama; Dian Noviyanti; Edward Hariyadi; Irfan Kurnia; Yesi Anggriani; Sakina Munira; Sara Uzlifah; Yusrawati Yusrawati; Bobby Indra Utama; Vaulinne Basyir; Rina Gustuti; Sukri Rahman; Mela Aryati; Rena Afri Ningsih; Rezi Liawati (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2026)
Maternal mortality and stunting remain major public health challenges in Indonesia, largely due to limited early detection of pregnancy complications and low maternal health literacy during the First 1000 Days of Life. Strengthening maternal knowledge through structured education is essential to improve pregnancy outcomes. This community service program aimed to enhance pregnant women’s knowledge of pregnancy danger signs, completion of six antenatal care (ANC) visits, anemia prevention, balanced nutrition, and early stunting prevention. A community-based participatory approach using a service-learning model was implemented among 39 pregnant women at Pauh Primary Health Center, Padang. Educational activities were conducted through interactive lectures, group discussions, and question-and-answer sessions. Knowledge was assessed using pre-test and post-test instruments and analyzed with a paired t-test. The results showed a significant increase in mean knowledge scores from 77.98 ± 16.26 to 86.60 ± 11.18 (p = 0.0002). The proportion of participants with “good” knowledge increased from 66.6% to 76.6%, while those with “poor” knowledge decreased substantially. These findings indicate that interactive and structured maternal health education effectively improves understanding of pregnancy complications and stunting prevention. Continuous implementation through routine maternal classes and stronger family involvement is recommended to sustain behavioral changes and improve maternal and child health outcomes.